The effect of infra slow frequency neurofeedback on quantitative electroencephalogram and autonomic nervous system function in adults with anxiety and related diseases - Du Toit, Prof Peet (University of Pretoria, 2026)
Dissertation (MSc)--University of Pretoria, 2018.